Simulation and Analysis of Airflow in ACMV System at G3 Building UTHM - Bahrin, Aiman; Binti M Amin, Sri Yulis (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Feeling sleepy and cannot pay full attention during class is one of the problems faced by student when studies inside lecture or classroom. That are one of the reasons students says when cannot performing well in their studies. The symptoms that shown by the student indicate there are sick building syndromes inside the buildings. To confirming the symptoms related to sick buildings syndromes, an analysis is made based of the air flow inside a lecture room. A model is created based on the actual lecture room in one of the main buildings in UTHM. The model was created using the computer aided design software SolidWorks. To stimulate the model and analyze the data a computational fluid dynamics (CFD) simulation was use by using software ANSYS FLUENT. The CFD simulation was focus on the three main parameters which is temperature, air velocity and the relative humidity. From the simulation, the results are for the temperature is 27 oC, as for the air velocity is 0.55 ms-1 and for the relative humidity is 75%. Then the results we compared to authorities’ bodies. The requirement is from Malaysia Standard (ICOP-2010) and ASHRAE Standard 55-2013. The comparison is to check whether the air flow inside the lecture room following the requirement from the authority’s bodies. From the comparison a percentage of error for temperature, air velocity and relative humidity is calculated. The percentage were 3.85%, 10% and 7%.